Investigating comparative polymerase chain reaction for antigen receptor rearrangement analysis in different types of feline lymphoma samples - Siripoonsub, Jedsada; Techangamsuwan, Somporn; Sirivisoot, Sirintra; Radtanakatikanon, Araya; Rungsipipat, Anudep (Frontiers in Veterinary Science, 2024)
Cats have the highest incidence of lymphoma among all animal species. Lymphoma accounts for 41% of all malignant tumors in cats and is responsible for 90% of hematopoietic tumors in felines. Biopsies are considered the gold standard for diagnosis. Polymerase chain reaction (PCR)-based clonality assessment of antigen receptor gene rearrangements can be a valuable complementary tool for identifying infiltrating B-and T-lymphocyte clones. Many studies have focused on intestinal cases but few have addressed mediastinal lymphoma. This study aims to: (1) investigate the clonality patterns of lymphoma samples from various anatomical sites, with a particular focus on mediastinal lymphoma, and (2) evaluate the sensitivity and specificity of the clonality analysis of pleural effusion samples in comparison with cytology, histology, immunohistochemistry, and immunocytochemistry for diagnosing mediastinal lymphoma. There were 82 cases, divided into 49 formalin-fixed and paraffin-embedded biopsy specimens (FFPE), 22 cell pellets, and 11 fresh tissue. This study examined the sensitivity and specificity of PCR for antigen receptor rearrangement (PARR) compared to immunohistochemistry (IHC) and immunocytochemistry. For T-cell receptor gamma chain genes, PARR demonstrated a sensitivity of 58.33% for both fresh tissue and FFPE samples, with a specificity of 100%. Cell pellet analysis exhibited a sensitivity of 64.71% and maintained 100% specificity. A combined analysis of fresh tissue and FFPE with cell pellets showed a sensitivity of 62.07%. For IGH, the sensitivity for fresh tissue and FFPE samples was 56.25%, while cell pellet analysis showed a sensitivity of 62.50%. When considering fresh tissue and FFPE samples, the sensitivity was 57.14%. In conclusion, molecular techniques have emerged as valuable tools for detecting lymphoma, especially in cases where traditional diagnostic methods yield inconclusive results, such as mediastinal lymphoma. While biopsy may not always be feasible, cytology and cell pellets obtained from pleural effusion offer alternative immunocytochemistry and molecular analysis samples, provided they are of sufficient quality and quantity. All sample types considered in this study were suitable for PARR to aid in cases with inconclusive results. Therefore, the sample selection should be tailored to the clinical situation.